2018
DOI: 10.1097/aog.0000000000002779
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Doppler Velocimetry During Individually Prescribed Exercise in Pregnancy

Abstract: Individually prescribed exercise according to guidelines for pregnant women does not adversely alter uterine artery Doppler values, suggesting that uterine blood flow is not reduced as a result of exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Furthermore, in the present study, a bout of exercise of moderate intensity resulted in decreased mean UtA PI centiles in women with GDM but not in women with uncomplicated pregnancies. Regarding uncomplicated pregnancies, in the past, similarly to the findings of the present study, a bout of exercise of moderate intensity in pregnant women with uncomplicated pregnancies did not affect UtA PI centiles before and after exercise [37]. In fact, UtA PI was investigated in the present study because it is a marker of pregnancy health integrating and reflecting the state of different systems of maternal and fetal physiology, including utero-placental circulation and endothelial function, which are involved in highrisk pregnancies and more particularly GDM pregnancies [38,39].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, in the present study, a bout of exercise of moderate intensity resulted in decreased mean UtA PI centiles in women with GDM but not in women with uncomplicated pregnancies. Regarding uncomplicated pregnancies, in the past, similarly to the findings of the present study, a bout of exercise of moderate intensity in pregnant women with uncomplicated pregnancies did not affect UtA PI centiles before and after exercise [37]. In fact, UtA PI was investigated in the present study because it is a marker of pregnancy health integrating and reflecting the state of different systems of maternal and fetal physiology, including utero-placental circulation and endothelial function, which are involved in highrisk pregnancies and more particularly GDM pregnancies [38,39].…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, fetal well-being was preserved because of the maintenance of uterine oxygen uptake. The findings in human studies are equivocal with some researchers reporting no change in uterine blood flow (22,42,46) and others reporting decreased uterine blood flow with no associated fetal compromise (43,54,56). A systematic review by Skow et al (50) concluded that acute or chronic exercise does not negatively affect fetal HR and uterine blood flow.…”
Section: Effect Of High-intensity Exercise On Uterine Blood Flowmentioning
confidence: 99%
“…In recent years, the impact of physical activity during pregnancy on uterine-placental blood flow perfusion has caused widespread concern among scholars. Szymanski et al found that the mean uterine artery Doppler indices (pulsatility index, resistance index, systolic/diastolic ratio) did not significantly change during moderateintensity exercise (40-59% of heart rate reserve) according to the exercise guidelines of pregnant women, which indicates that after routine exercise, uterine arterial blood flow is not reduced (Szymanski and Kogutt 2018). However, after vigorous-intensity exercise (60-84% of heart rate reserve), all mean uterine artery Doppler indices showed reductions, which may cause decreased in uterine blood flow and may adversely affect fetal health.…”
Section: Impact Of Physical Activity On the Pathophysiology Of Gestatmentioning
confidence: 99%